2014
DOI: 10.4103/0972-124x.128190
|View full text |Cite
|
Sign up to set email alerts
|

Can MTA be: Miracle trioxide aggregate?

Abstract: Mineral trioxide aggregate (MTA) has been used for more than 10 years in the dental community and has often been thought of as a material of choice for the endodontist. The dental pulp is closely related to periodontal tissues through apical foramina, accessory canals, and dentinal tubules. Due to this interrelationship, pulpal diseases may influence periodontal health and periodontal infections may affect pulpal integrity. It is estimated that pulpal and periodontal problems are responsible for more than 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 21 publications
0
23
0
4
Order By: Relevance
“…Sealing the perforation defect is an important step in limiting bacterial contamination [1]. Among the various available materials to seal perforations, MTA is the optimal choice for the procedure due to its biocompatibility, great sealing ability and adaptation to the dentinal wall, high pH, and ability to release calcium ions [2][3][4]. MTA applications can also induce hard tissue formation (dentin, cementum, and bone) and can facilitate periodontal tissue regeneration [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sealing the perforation defect is an important step in limiting bacterial contamination [1]. Among the various available materials to seal perforations, MTA is the optimal choice for the procedure due to its biocompatibility, great sealing ability and adaptation to the dentinal wall, high pH, and ability to release calcium ions [2][3][4]. MTA applications can also induce hard tissue formation (dentin, cementum, and bone) and can facilitate periodontal tissue regeneration [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various available materials to seal perforations, MTA is the optimal choice for the procedure due to its biocompatibility, great sealing ability and adaptation to the dentinal wall, high pH, and ability to release calcium ions [2][3][4]. MTA applications can also induce hard tissue formation (dentin, cementum, and bone) and can facilitate periodontal tissue regeneration [2][3][4][5]. Pace et al reported that 90% of perforation treatments using MTAs show periodontal and bone healing after 6 months, visible through the decrease in radiolucency in X-ray photos [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no material has met all the above-mentioned criteria and no evidence exists regarding definite superiority of one material over the others. 10 The compressive strength of Pro-root MTA is 67.3 MPa after 21 days incubation in water and for white MTA Angelus is 44.2 MPa after 28 days of immersion in water, 11 which are higher than those of the spongy bone (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and lower than those of the cortical bone (150-200 MPa) 12 In a summary, excellent biocompatibility, release of calcium ions, high pH, excellent sealability of the root canal system, induction of hard tissue formation, radiopacity, setting ability in the presence of moisture, antibacterial properties, insignificant toxicity, very low solubility in body fluids and optimal dimensional stability and adaptation to tooth structure have all contributed to the extensive use of MTA in dental procedures. 2,3 The major ingredients of MTA cements are tricalcium silicate, dicalcium silicate, tricalcium aluminate, tetracalcium aluminoferrite, and a slight amount of bismuth oxide (for the purpose of radiopacity).…”
Section: Introductionmentioning
confidence: 99%
“…An ideal root-end filling material must be biocompatible, capable of providing a hermetic coronal seal, have suitable handling properties and guarantee a long-term successful clinical service. 9 In addition, MTA cement could act as an antibacterial agent because the process of biodegradation develops an alkaline microenvironment, which eliminates microorganisms. [1][2][3] The introduction of mineral trioxide aggregate (MTA) as a root-end filling material gained significant attention among scientist worldwide because MTA cements have been proven to be bioactive and, at the same time, capable of sealing all the communications between the root canal system and the external root surfaces in an effective way.…”
Section: Introductionmentioning
confidence: 99%